1999
DOI: 10.1159/000069412
|View full text |Cite
|
Sign up to set email alerts
|

Creutzfeldt-Jakob Disease Mortality in Italy, 1982–1996

Abstract: We report an estimate of Creutzfeldt-Jakob disease (CJD) deaths in Italy from 1982 to 1996 by using mortality data based on a retrospective review of deaths taken from the mortality data base of the Italian Census Bureau (ISTAT, years 1982–1993), and on the prospective surveillance performed by the Italian National Register of CJD (years 1993–1996). One hundred and ninety-five and 154 deaths attributed to CJD were recorded by ISTAT and the CJD register, respectively. The average annual age-adjusted mortality r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
2
2
0
Order By: Relevance
“…The increase may have been accompanied to some extent by the improvement of physicians' diagnostic skills for CJD since 1997 when a manual for clinical practice on CJD was introduced in our country. 20,21 Consistent with the previous findings, [22][23][24][25][26][27][28] the present study showed that the CJD mortality rates rapidly increased with age between 50 and 74 years, especially among females, and sharply declined at 80+ years of age, although the causal mechanism remains unexplained. These findings were comparable with those for patients with CJD reported to the Surveillance.…”
Section: Location Of Deathsupporting
confidence: 90%
“…The increase may have been accompanied to some extent by the improvement of physicians' diagnostic skills for CJD since 1997 when a manual for clinical practice on CJD was introduced in our country. 20,21 Consistent with the previous findings, [22][23][24][25][26][27][28] the present study showed that the CJD mortality rates rapidly increased with age between 50 and 74 years, especially among females, and sharply declined at 80+ years of age, although the causal mechanism remains unexplained. These findings were comparable with those for patients with CJD reported to the Surveillance.…”
Section: Location Of Deathsupporting
confidence: 90%
“…The most important finding of this study is that the activity of the CJD register was improved, as previously predicted, from 1996 onward [14]. In 1999, the last year of survey, the underreporting of human TSEs to the CJD register was estimated in less than 6% and it is likely that this positive trend would continue in the following years.…”
Section: Discussionsupporting
confidence: 75%
“…CJD ascertainment from death certificates is unreliable, with misclassification reaching 35.6% in 1 year in Italy [16]. In Ireland, if definite cases alone (i.e only autopsy-confirmed cases) were included prior to mid 1996, 8 cases would have been identified, giving an annual incidence of 0.13/million, a figure below that of other European countries for the equivalent time period.…”
Section: Discussionmentioning
confidence: 99%